2004
DOI: 10.1242/jcs.01276
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid residues on astrocytes regulate neuritogenesis by controlling the assembly of laminin matrices

Abstract: In the developing nervous system migrating neurons and growing axons are guided by diffusible and/or substrate-bound cues, such as extracellular matrix-associated laminin. In a previous work we demonstrated that laminin molecules could self-assemble in two different manners, giving rise to matrices that could favor either neuritogenesis or proliferation of cortical precursor cells. We investigated whether the ability of astrocytes to promote neuritogenesis of co-cultivated neurons was modulated by the assembli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Deposited on Coverslip-Although laminin aggregates could not be detected in neutral pH at 50 g/ml, we have previously demonstrated that deposits of the aggregated protein became visible when the laminin solution was incubated over the surface of a glass coverslip (11,14). Such deposits were characterized by immunostaining and shown to be morphologically different from others obtained in acidic pH.…”
Section: Effect Of Laminin Fragments On Laminin Matricesmentioning
confidence: 93%
See 2 more Smart Citations
“…Deposited on Coverslip-Although laminin aggregates could not be detected in neutral pH at 50 g/ml, we have previously demonstrated that deposits of the aggregated protein became visible when the laminin solution was incubated over the surface of a glass coverslip (11,14). Such deposits were characterized by immunostaining and shown to be morphologically different from others obtained in acidic pH.…”
Section: Effect Of Laminin Fragments On Laminin Matricesmentioning
confidence: 93%
“…In the nervous system, for instance, it has been demonstrated that laminin goes from cell-associated to scattered extracellular matrix deposits or from a punctated pattern to small or large sheet-like aggregates in developing brain (4,12). Cells in culture can also assemble different networks as demonstrated for midbrain and cortical neural cells (13,14) or Schwann cells (15). In addition, we have previously described that the laminin matrix synthesized by embryonic astrocytes (which efficiently supports neurite outgrowth) resembles the artificial matrix assembled upon laminin acidification because it is flat, organized, and closely associated to the cell surface (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocytes, the most abundant glial cell type, produce most of the extracellular matrix components and neurotrophic factors in the central nervous system that are involved in axonal growth (18,19,22,32), neuronal proliferation, survival, and stem cell fate determination (14,19,20,26,(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…For example, the inhibition of nerve regeneration mediated by myelin-associated glycoprotein has been shown to involve clustering of gangliosides (43). In another model, the assembly of laminin on the surface of astrocytes in culture as well as the laminin-induced neuritogenesis of primary neurons cultivated on them have been shown to be controlled by the local acidic pH provided by sialic acid-containing lipid rafts on the membranes of astrocytes (44,45).…”
Section: A Inset)mentioning
confidence: 99%